Pencegahan Kesehatan Mental dalam Upaya Mengurangi Stigma Kesehatan Mental di Masyarakat - Maria Krisinta Adventinawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Mental health is very important for society and individuals. However, the stigma of mental illness remains a major barrier for those who need support and treatment. Self-, social, and structural stigma are types of stigma that contribute to isolation and discrimination. The aim of this research is to find out how education and awareness campaigns can prevent the stigma of mental disorders. The methods used include analysis of literature on biological, psychological, and social variables that influence mental health, as well as analysis of primary, secondary, and tertiary prevention methods. The results show that public education, awareness campaigns, and programs in schools based on social media can significantly increase public understanding and reduce unfavorable stereotypes. In conclusion, preventing mental disorders requires a broad approach that includes education, early detection, and community-based intervention. In this way, society can create a friendly, supportive and stigma-free environment to improve everyone's mental well-being.